Novel compound heterozygous variants in the USH2A gene associated with autosomal recessive retinitis pigmentosa without hearing loss - Huang, Yanxia; Yuan, Lamei; He, Guiyun; Cao, Yanna; Deng, Xiong; Deng, Hao (Frontiers in Cell and Developmental Biology, 2023)
Retinitis pigmentosa (RP) is a group of progressive inherited retinal dystrophies characterized by the primary degeneration of rod photoreceptors and the subsequent loss of cone photoreceptors because of cell death. It is caused by different mechanisms, including inflammation, apoptosis, necroptosis, pyroptosis, and autophagy. Variants in the usherin gene (USH2A) have been reported in autosomal recessive RP with or without hearing loss. In the present study, we aimed to identify causative variants in a Han-Chinese pedigree with autosomal recessive RP. A full clinical examination, whole exome sequencing, and Sanger sequencing, as well as co-segregation analysis were performed. Novel compound heterozygous variants in the USH2A gene, c.3304C>T (p.Q1102*) and c.4745T>C (p.L1582P), were identified as the genetic causes. The findings may enhance the current knowledge of the pathogenesis of USH2A-associated phenotypes, expand the spectrum of the USH2A gene variants, and contribute to improved genetic counseling, prenatal diagnosis, and disease management.